Mitigating Cyber Attacks Through Security Models and Networking Protocols - Chaudhary, Pranav (International Journal of Computer Sciences and Engineering, 2025)
With the increasing dependency of most of the organizations on technology in today’s world, the aspect of information security is a major concern. A plethora of data, be it insignificant (like text messages) or vital (data of some government agency) is stored and transferred over the internet and is exposed to a variety of attacks by people with immoral intentions. Information security is therefore a vital aspect for any organization or government body which has to ensure that their data is not mutated by an attacker and reaches the intended recipient unchanged. This paper discusses various types of security models which are used in practice by the organizations and various cryptographic methods that are commonly used for the protection of data against undesirable breaches. A variety of algorithms have been developed in order to protect the data. Various types of keys which form an essential component of the encrypting algorithms are also discussed. There are several cyber-attacks which pose an austere threat to the organizations. These threats can be mitigated using various cryptographic algorithms and network protocols. These protocols also play an important role in mitigating the security breaches of sensitive data and are discussed towards the end of this paper.